Feasibility of simultaneous integrated boost for high-dose treatment of high-risk prostate cancer - E. S. Sukhikh; L. G. Sukhikh; A. V. Taletsky; Zh. A. Startseva; V. V. Verkhoturova; V. V. Rozanov; E. A. Selikhova (Сибирский онкологический журнал, 2023)
Background. Radiation therapy for high-risk prostate cancer presents a challenge for cancer radiotherapists. The improvement of treatment outcomes is associated with radiation dose escalation and prophylactic irradiation of lymph nodes, therefore, the development of the new treatment schemes is needed. Simultaneous integrated boost technique based on the volumetric modulated arc therapy is the most efficient treatment option. Material and Methods. The anatomical data of 10 patients with high-risk prostate cancer was used for dosimetry-based treatment planning. Both simultaneous integrated boost and sequential boost technique were considered. The treatment planning goal was to deliver the equivalent dose of 96 Gy at 2 Gy per fraction (EQD2=96 Gy) (α/β=1.5 Gy) to the prostate, EQD2=62.5 Gy to the seminal vesicles and EQD2=50 Gy to lymph nodes avoiding damaging the organs at risk, mainly the bladder and rectum. The irradiation was based on volumetric modulated arc therapy with two partially coplanar arcs and two rotations at each arc. The obtained dose distributions were compared with respect to dose-volume histograms and equivalent uniform doses (EUD). Results. In the case of sequential boost, the minimal dose delivered to the prostate was equal to 95.9 ± 2.1 Gy, EUD=104.9 ± 1.7 Gy. The dose delivered to 2 cm3 (D2cc) bladder was 97.4 ± 2.0 Gy. Normal tissue complication probability (NTCP) was 1.64 %. The dose delivered to 2 cm3 (D2cc) rectum was 103.4 ± 9.2 Gy and NTCP was 27.4 %. In the case of simultaneous integrated boost, the minimal dose delivered to the prostate was equal to 90.4 ± 2.3 Gy, EUD=103.9 ± 1.3 Gy. The bladder dose was as high as D2cc=96.1 ± 5.2 Gy, NTCP=0.176 ± 0.132 %, the rectum dose - D2cc=81.1 ± 6.0 Gy, NTCP=2.34 ± 1.92 %. Conclusion. Volumetric modulated arc therapy along with simultaneous integrated boost have shown the feasibility of simultaneous irradiation of the prostate, seminal vesicles and lymph nodes up to the prescribed dose values without significant over irradiation of the organs at risk (OARs). Dose values in the tumor as high as EUD=103.9 ± 1.3 Gy along with prophylactic irradiation of lymph nodes may result in higher tumor control probability value and should be considered for clinical trials.